Terapia física y rehabilitación: diagnóstico y control de lesiones tendoligamentosas en perros atletas con ultrasonografía musculoesquelética - Mercado, M. (2018)
The Agility competition is a canine sports specialty that is booming. The difficulty of this sport is to synchronize speed and quality of execution.The canines that practice this sport suffer injuries in their forelimbs. Tendon lesions, ligaments and synovial bursae are the most frecuently in these dogs because they must jump obstacles which can be the cause for claudication after competition and palpable liquid deformation.\nUltrasonography (US) musculoskeletal is a dynamic, non-invasive, low cost and does not require patient sedation.\nWe treated 5 Border Collie breed canines with diagnosed bursitis and elbow tendonitis confirmed by musculoskeletal ultrasonography. The Simple Descriptive Pain Scale was used to assess pain. Goniometry was performed to evaluate functionality of the elbow joint. Physiotherapy protocol: Relative rest, Cryotherapy 5 minutes (daily application), LASER semiconductor gallium arsenide, dose of 8 J / cm2, pulsatile therapeutic ultrasound 1 Mhz, dose 0.5 W / cm2 5 minutes. 2 sessions per week, a total of 24 sessions. For the statistical analysis, the Wilcoxon test was applied.\nThe aim of this work was to observe the efficiency of the physiotherapy protocol for lesions tendo ligaments by means of musculoskeletal ultrasonography.